Tafsir Ekologi Syekh Ali Jum’ah: Merespon terhadap Kebijakan Nahdlatul Ulama Terkait Perizinan Konsesi Tambang Batu Bara - Muhamad Firdaus; Ahmad Reza Wibowo (Lembaga Penelitian, Penerbitan, dan Pengabdian Masyarakat (LP3M) Institut Agama Islam Bakti Negara (IBN) Tegal, 2025)
This article discusses the method of ecological interpretation represented by Syeikh Ali Jum’ah in his work al-Bi’ah Wa al-Hifdzu ‘Alaih Min Manarin Islamiyin. The main objective of this research is to see the characteristics of Sheikh Ali Jum’ah’s interpretation method of verses related to ecological issues. Furthermore, implementing the results of the interpretation of the method to respond to NU’s policy in taking the coal mining concession permit on May 30, 2024. The research method uses qualitative and library research approach. This study concludes that Sheikh Ali Jum’ah’s ecological interpretation method has a Maudhu’i-Isyari style using the Eko-Fiqhi approach based on the principles of al-haq and al-Wajib, from both of which gave birth to a new concept called huquq al-Bi’ah and Wajib al-Bi’ah. Furthermore, it concludes that NU’s policy in accepting coal mining concessions is not in line with the principles of ecological interpretation of Syeikh Ali Jum’ah so that on this basis NU must withdraw the license.